PERANAN TENAGA KERJA PEREMPUAN DALAM MENINGKATKAN NILAI TAMBAH DAN KESEJAHTERAAN NELAYAN TRADISIONAL DI MALUKU - Latuconsina, Asmaria (Jurnal Organisasi Dan Manajemen, 2011)
In Maluku there were small scale traditional food processing activities for fisheries product such as curing and drying, which has a great potential to be developed. This study aims to identify the determinants of food processed, and the role of female labor in increasing family welfare of traditional fishermen. This descriptive study was done in four districts, namely: Leihitu, Banda, West Seram, and East Seram. A business unit was used for analysis with purposive and random sampling. The results showed that processed output was determined mainly by the husbands catches and purchased fish. Business scale in all districts was economically rational decisions and could be improved because it shows the increasing return to scale. Processing jobs are mostly done by woman. Value added created could be used to cover most of the monthly household expenses, and improve the family welfare, which were characterized by permanent and semi-permanent houses occupied, and increasing level of education of family members. However, the fishermen welfare could be increased more by incorporating fish cage system in their aquaculture to increase inputs and improving marketing strategy.